The road to FMFM 1: the United States Marine Corps and maneuver warfare doctrine, 1979-1989 - Damian, Fideleon II (Kansas State University, 2008)
In 1989, the United States Marine Corps published the document Fleet Marine Force Manual 1, Warfighting. Its appearance signaled the official adoption of maneuver warfare as the Corps's organizational philosophy and the basis of its doctrine for preparing and conducting operations. The decade of debate and experimentation that preceded the publication of Warfighting has not received detailed examination, but merits such for the insights it can provide to understanding intellectual change and military reform. Beginning in 1979, Marine Corps officers engaged in an intraservice debate over the issue of maneuver warfare, a new concept that began to circulate among military reformers in the latter half of the 1970s. A group of Marine officers known as "maneuverists" began meeting in unofficial seminars to study, refine, and promote the idea. Maneuverists believed that maneuver warfare was a more fluid and dynamic way of fighting because it stressed flexibility, creativity, and a focus on enemy behavior. They also thought the new idea offered a more effective alternative for fighting war than contemporary practices, which they thought focused too much on rigid application of standardized procedures and methods of existing manuals. The intellectual transformation of the Marine Corps involved three main mechanisms. The first was a theoretical mechanism centered on public debate in the pages of Marine Corps Gazette to introduce and defend maneuver warfare to Marine audience. The second was a functional/practical mechanism that involved educational and training initiatives at the Amphibious Warfare School and Camp Lejeune, North Carolina. The third mechanism was the use of institutional authority made possible with the appointment of General Alfred M. Gray, a senior and vocal maneuver warfare champion, to the position Commandant of the Marine Corps. Using the authority of his office, Gray directed the writing of a doctrinal manual encapsulating the ideas of maneuver warfare to provide the Corps organizational focus and direction. The resulting manual FMFM 1, Warfighting, officially adopted maneuver warfare as service doctrine and organizational warfighting philosophy.
Keywords: United States Marine Corps; Maneuver Warfare; Military Doctrine; Military Thought; warfighting; FMFM 1; History, United States (0337)